The vulva: Physiology and clinical management - Farage, Miranda A.; Maibach, Howard I. (CRC Press, 2017)
Compilation unique d'expertise sur l'anatomie, la physiologie, les questions cliniques et la recherche actuelle, ce manuel analyse la diversité des présentations en fonction de l'âge, de l'origine ethnique, des symptômes, des troubles, des diagnostics et de la toxicité. La deuxième édition de cette ressource essentielle pour toute personne prenant soin de patientes a été doublée pour inclure des chapitres supplémentaires. Tous les médecins, qu'ils soient dermatologues ou gynécologues, ainsi que ceux qui recherchent les preuves scientifiques et les symptômes, bénéficieront de l'expérience des contributeurs et éditeurs experts réunis ici.
Keywords: 2000 à aujourd'hui; corps; dermatologie; discipline; gynécologie; médecine; projet charge mentale; périodes historiques; santé; santé menstruelle; santé reproductive; santé sexuelle; sciences; sexualité; sexualité des femmes*; thématiques

Sex and gender considerations in transplant research: A scoping review - Laprise, Claudie; Cole, Katherine; Sridhar, Vikas Srinivasan; Marenah, Tida; Crimi, Cassandra; West, Lori; Foster, Bethany J.; Pilote, Louise; Sapir-Pichhadze, Ruth (Transplantation, 2017)
Background Despite the growing appreciation of the importance of sex and gender considerations in transplantation research, there is currently no framework or good practice guidelines for the appropriate handling of sex and gender issues in human allotransplantation research. Methods We will conduct a scoping review to synthesize the evidence on how matters of sex and gender have been handled in human allotransplantation research. We will survey the literature discussing sex and gender in relation to transplantation, including adult and pediatric patients, hematopoietic and solid organ transplant recipients as well as organ donors. We will search MEDLINE and Embase for literature discussing sex and gender in relation to transplantation. Two reviewers will independently evaluate the eligibility of all identified titles and abstracts for inclusion in the full text review, as well as data extraction. Descriptive data and information on how sex and gender have been considered in human transplantation research will be reported. Discussion This scoping review will be an important stepping stone towards the development of good practice guidelines on study design and analysis considerations when handling sex and gender issues in human transplantation research. This scoping review can also help identify methodological issues that restrict the translation of transplantation research findings into clinical practice related to underestimation of sex/gender differences. This review will ultimately identify major gaps, inform donor-recipient selection, guide personalized interventions, and prioritize research recommendations in human transplantation research. Electronic supplementary material The online version of this article (10.1186/s13643-017-0578-4) contains supplementary material, which is available to authorized users. Keywords: Sex, Gender, Transplantation, Scoping review
Keywords: 2000 à aujourd'hui; corps; discipline; médecine; projet charge mentale; périodes historiques; ressource en ligne; santé; sciences; thématiques; transplantation

À qui appartient-il de déterminer les modes d’intervention auprès des personnes intersexuées ? - Bastien Charlebois, Janik (Nouvelles pratiques sociales, 2016)
Les personnes intersex(ué)es sont au coeur de tensions dans l’orientation des pratiques médicales sur leur corps et la détermination de leur « propre bien ». La volonté d’autodétermination relayée par les acteurs sociaux politisés et les critiques qu’ils formulent à l’endroit des médecins se heurtent au déficit de crédibilité que celle-ci leur accorde. En isolant certains des motifs les plus solides du maintien de la primauté médicale sur l’orientation des pratiques, nous relevons les arguments développés par la communauté intersexe pour y répondre. Cette réflexion est menée à partir des perspectives philosophiques de Young sur l’autodétermination et du concept d’injustice épistémique de Fricker.
http://www.erudit.org/fr/revues/nps/2016-v28-n1-nps02990/1039174ar/
Keywords: approches et analyses; autodétermination; corps; cours; discipline; fem1000; histoire et politique; identités LGBTQIA2+; lit4700; militance; médecine; personnes intersexes; point de vue situé; premier cycle; ressource en ligne; sciences; thématiques

Gender matters in biological research and medical practice ∗ - Schiebinger, Londa; Stefanick, Marcia L. (Journal of the American College of Cardiology, 2016)
Keywords: 2000 à aujourd'hui; 2010-2019; corps; discipline; médecine; méthodologie; projet charge mentale; périodes historiques; santé; sciences; thématiques